STUDI PERAN UMKM DALAM PENGOLAHAN SUMBER DAYA ALAM LOKAL UNTUK MENDUKUNG EKONOMI PERTANIAN BERKELANJUTAN - Ernah; Nur Hopifah, Asiyah; Fajar Febrian, Mochamad Rizky; Prameshwari, Jasmine Nadiva (Jurnal AGRIBIS, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in processing local natural resources into value-added products that contribute to sustainable agricultural economic development.This study aims to analyze the strategic role of MSMEs in transforming agricultural products into competitive innovative products, and to identify supporting factors such as access to technology, training, and government policies.This study also discusses the positive impact of MSMEs on environmental conservation and improving community welfare.The results of this study indicate that government support through training, coaching, and facilitation of global market access is the key to the success of developing MSMEs based on local resources.These findings are expected to provide strategic recommendations to encourage the development of MSMEs that are oriented towards economic and environmental sustainability in the agricultural sector.